Prevalence of periodontal disease among students attending selected secondary schools in Enugu-East LGA, Enugu State, Nigeria - Johnson John Omale; Vasileios Margaritis; Balarabe Musa Hussain; Justina Nnena Ngwu; Angela N. Ohadoma; Chijioke Peter Nwosu; Scholastica Chidi Okoli; Samuel A. Ani (Orapuh, Inc., 2021)
Introduction Chronic periodontal disease is highly prevalent among Nigerians. The disease process can have adverse effects on students. Finding out the prevanlence of periodontal disease among students may help in the planning of intervention. Purpose This study was aimed at assessing the prevalence of periodontal disease among students attending selected secondary schools in Enugu-East LGA, Enugu State, Nigeria. Materials and Methods The study was carried out between May and June, 2014 as part of PhD dissertation submitted to Walden University. Three school types (public, private and faith-based/missionary) were involved in the study; 12 schools (4 from each of the school types) were selected for the study with the students between aged 11-17 years. Proportional stratified sampling technique was adopted to select 20 students from JSS I, II, and III , respectively, from each of the schools ( a total of 60 students from each of the selected schools), making a total of 720 students, but only 671 students that indicated interest in the study by filling informed consent form (361 males and 310 females) were involved in the study. Data was collected using intraoral examination by adopting the periodontal disease index (PDI). Data were analyzed using the statistical package for social sciences (SPSS) version 21.0. Bivariate non-parametric tests (Mann Whitney test and Kruskal-Wallis test) were used to determine the normality of the PDI collected. Results Results showed that periodontal disease was not prevalent among the students with a general mean PDI of 1.15. Males had a higher mean PDI (1.16) than females with a mean PDI of 1.13. Students within the age range '11-12 years old' had a higher mean PDI (1.27) than the other age groups. Students from missionary schools had lower levels of periodontal disease than those from public schools, with an odds ratio of 0.612 (95% CI [0.402, 0.934]). Students from the JSS III class tended to have a lower level of periodontal disease than those of the JSS I class (OR: 0.567, 95% CI [0.363, 0.886]). Conclusions The incorporation of oral health promotion programmess into school curricula may increase the adoption of preventive oral health strategies by students (such as regular dental attendance), to maintain their good oral health for a lifetime